2018
DOI: 10.1002/ange.201809410
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Amphiphiles Induce Macromolecule Denaturation and Organelle Decomposition in Pathogenic Yeast

Abstract: Cationic amphiphiles are alarge and diverse class of antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…First, 2j was incubated at 32 μg/mL, which is one, 1/4, and 1/2 of the MICs against F. graminearum, C. albicans MYA2876, and C. albicans 64124, respectively (Figure 3). Interestingly, fluorescence from 2j closely resembled previously reported images 30 and was observed to physically associate with cells of F. graminearum and the two C. albicans strains within 5 min of initial exposure. Therefore, it is likely that AKs not only caused fast membrane permeabilization but also quickly interacted with cells at concentrations lower than the corresponding MICs.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…First, 2j was incubated at 32 μg/mL, which is one, 1/4, and 1/2 of the MICs against F. graminearum, C. albicans MYA2876, and C. albicans 64124, respectively (Figure 3). Interestingly, fluorescence from 2j closely resembled previously reported images 30 and was observed to physically associate with cells of F. graminearum and the two C. albicans strains within 5 min of initial exposure. Therefore, it is likely that AKs not only caused fast membrane permeabilization but also quickly interacted with cells at concentrations lower than the corresponding MICs.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…A recent report showed that AKs incorporated with fluorophores "rapidly accumulated in the cytosol and led to structural changes in proteins and DNA". 30 In the current study, we chose to use hydrophobic fluorophores instead of an alkyl chain/fluorophore combina-tion so that the overall structures of 2i and 2j would more closely resemble the amphipathic structural features of the AKs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous study has reported that cationic amphiphiles could induce organelle decomposition and denaturation of protein and DNA through a necrotic process [13] . Therefore, we continued to examine if PGOx 10 similarly influenced the integrality of representative fungal organelles, such as the nucleus and mitochondria.…”
Section: Resultsmentioning
confidence: 98%
“… 47 To ask if the antifungal activity of COL also is dependent upon its peptide charge, we tested three additional membrane-disrupting antimicrobials with different net charges for their ability to synergize with FLC ( Figure S9 ). Similar to COL (charge +5 47 ), RB163, a cationic amphiphile-derived from the aminoglycoside antibiotic tobramycin 48 (compound 3 in ref ( 48 )) synergized with FLC (FICI = 0.28 with 0.125 μg/mL FLC and 4 μg/mL RB163). By contrast, daptomycin (charge −3) 49 ( Figure S9C ) did not augment the activity of FLC.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-exposed cultures were diluted 1:100 for 2–3 h in casitone followed by drug addition. Drugs were diluted in water (posaconazole (Sigma-Aldrich SML2287, >98%), colistin (Glentham Life Sciences GA9867, ≥19 000 U/mg), amphotericin B (TOKU-E, ≥95%), 5-fluorocytosine (Sigma-Aldrich F7129, ≥99%); ethanol (terbinafine T8826, ≥98%), fluconazole (Sigma-Aldrich F8929, ≥98%, ketoconazole (Sigma-Aldrich K1003, ≥99%), miconazole (Fischer Bioreagents, 98%), clotrimazole (Glentham Life Sciences, GA8137), caspofungin diacetate (Sigma-Aldrich SML0425, ≥19 000 IU/mg), anidulafungin (Sigma-Aldrich SML2288, ≥97%) myriocin (Sigma-Aldrich M1175, ≥98%), amphotericin B (A2411, ∼80%), daptomycin (Sigma-Aldrich D2446, ≥90%), RB163 48 (≥95%)) or DMSO (natamycin, Sigma-Aldrich, ≥95%). Casitone solid media (casitone liquid plus 10 g/L agar (Formedium, Ltd.)) was used for the disk assay method.…”
Section: Methodsmentioning
confidence: 99%